2018
DOI: 10.1007/s11104-018-3667-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity in root litter and soil legacies differentially affect legume root traits

Abstract: Background and AimsPlants affect the soil environment via litter inputs and changes in biotic communities, which feed back to subsequent plant growth. Here we investigated the individual contributions of litter and biotic communities to soil feedback effects, and plant ability to respond to spatial heterogeneity in soil legacy.MethodsWe tested for localised and systemic responses of Trifolium repens to soil biotic and root litter legacy of seven grassland species by exposing half of a root system to control so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Arbuscular mycorrhizal (AM) fungi [ 4 , 5 ] and root traits (e.g. root biomass and shoot: root ratio) [ 6 , 7 ] are both needed for plant nutrient acquisition, and their variation may reflect key nutrient acquisition behaviours in the belowground environment [ 8 10 ]. For example, plants will modify their biomass allocation in heterogeneous soil environments [ 11 ], and allocate more carbohydrates belowground for root proliferation and produce more roots in high nutrient availability patches [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arbuscular mycorrhizal (AM) fungi [ 4 , 5 ] and root traits (e.g. root biomass and shoot: root ratio) [ 6 , 7 ] are both needed for plant nutrient acquisition, and their variation may reflect key nutrient acquisition behaviours in the belowground environment [ 8 10 ]. For example, plants will modify their biomass allocation in heterogeneous soil environments [ 11 ], and allocate more carbohydrates belowground for root proliferation and produce more roots in high nutrient availability patches [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Selecting different patterns of space expansion were an important adaptive strategy for clonal plants to effectively utilize heterogeneous resources with improved survival rates and growth competitiveness, and it is also the result of the interaction between the biological characteristics of clonal plant population and environmental factors [33][34][35]. Environmental factors (water, salt, pH, nutritional conditions, and so on) are essential for the growth and spatial expansion of clonal plants in habitats with different resource levels [36][37][38][39]. Water use efficiency affects the morphological construction of plant leaves.…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneity of soil resources plays an important role in sustaining the structure and functioning of forest ecosystems [1][2][3], as such heterogeneity can impact the survival of colonizing individual vegetation species and thus the biodiversity of vegetation communities [4,5]. Plants can also impact the spatial pattern of soil resources by altering physical, chemical and biological soil properties [6][7][8]. However, recent studies have found that these interactions and the potential heterogeneity across landscapes could be modified by disturbances [9][10][11].…”
Section: Introductionmentioning
confidence: 99%